KATA GANTI DALAM TRANSKRIP WAWANCARA PANORAMA ANTARA MARTIN BASHIR DENGAN LADY DIANA - Sabana, Sasmitha; Pamantung, Rina P.; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Sasmitha Sabana1Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Dr. Rina P. Pamantung, M.Hum2Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Dr. Garryn Ch, Ranuntu, S.Pd, M.Hum3Â Â Â Â This research is entitled â€œPronouns in the transcript of Lady Dianaâ€™s Panorama Interview with Martin Bashirâ€. The aims of this research are to identify, classify, analyze and describe the meaning of â€œPronouns in the transcript of Martin Bashir Panorama Interview with Lady Dianaâ€. The descriptive method is used in this research and the data were collected from the transcript of the interview and analyzed based on the theory of William (2005). The result of this research shows that in the transcript there is six types of pronouns namely: personal pronouns, possessive pronouns, Reflexive pronouns, Demonstrative Pronouns, Indefinite Pronouns, Relative Pronouns. There is the meaning from six types of Pronouns, Personal pronoun are pronoun that are used to represent people or things. Possessive pronoun are pronoun that are used to help us show ownership in a sentence. Reflexive pronoun are words ending in self or selves to show oneself or someone else. Demonstrative pronoun is a pronoun that are used to point something in sentence. Indefinite pronoun are those one or more unspecified objects or things. Relative pronoun is pronoun that are used to connecting meaning in a sentence. This research can provide knowledge about the meaning of pronouns in syntax studies, especially for readers, and can help students of the Faculty of Humanities, especially students majoring in English Department to examine pronouns using different objects, also this research can be used as a reference for further research.——————————————-Keywords: Syntax, Pronouns, Lady Diana, Interview, Martin Bashir